2014
DOI: 10.1093/bioinformatics/btu074
|View full text |Cite
|
Sign up to set email alerts
|

The cleverSuite approach for protein characterization: predictions of structural properties, solubility, chaperone requirements and RNA-binding abilities

Abstract: Motivation: The recent shift towards high-throughput screening is posing new challenges for the interpretation of experimental results. Here we propose the cleverSuite approach for large-scale characterization of protein groups.Description: The central part of the cleverSuite is the cleverMachine (CM), an algorithm that performs statistics on protein sequences by comparing their physico-chemical propensities. The second element is called cleverClassifier and builds on top of the models generated by the CM to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 76 publications
1
89
0
Order By: Relevance
“…CleverMachine (Klus et al, 2014) allows for the detection of protein properties that differ between two datasets and has been used to distinguish P-bodies and stress granules from other globular proteins (Marchese et al, 2016) and to classify homo-repeat proteins (Yu Lobanov et al, 2016). A multi-cleverMachine property prediction and comparison of the RALFs reveals that the clade IV proteins differ in a variety of physico-chemical properties from the other clades (Figure S4), such as a reduced disorder propensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CleverMachine (Klus et al, 2014) allows for the detection of protein properties that differ between two datasets and has been used to distinguish P-bodies and stress granules from other globular proteins (Marchese et al, 2016) and to classify homo-repeat proteins (Yu Lobanov et al, 2016). A multi-cleverMachine property prediction and comparison of the RALFs reveals that the clade IV proteins differ in a variety of physico-chemical properties from the other clades (Figure S4), such as a reduced disorder propensity.…”
Section: Resultsmentioning
confidence: 99%
“…The online multi-cleverMachine tool (Klus et al, 2014) was used to compare the physico-chemical properties of RALF proteins. Unaligned sequences for each clade were uploaded to the server in FASTA format, with “clade IV” proteins being denoted as the positive set and clade I, II, and III proteins as negative sets.…”
Section: Methodsmentioning
confidence: 99%
“…cat RAPID signature exploits properties such as hydrophobicity, secondary structure, disorder, and burial . Each feature defines a unique signature , or profile, containing position‐specific information arranged in sequential order from the N‐ to the C‐terminus . In addition to the RNA‐binding score, cat RAPID signature predicts regions contacting RNA.…”
Section: Computational Methods For Detection Of Protein–rna Interactionsmentioning
confidence: 99%
“…26 Especially physicochemical properties of amino acids, such as structural disorder and polarity, are relevant to characterize the RNA-binding ability of proteins. 27,28 Indeed, recent studies reported that in addition to classical RNA-binding domains other regions found in ribosomal proteins, translation elongation factors, zinc fingers as well as structurally disordered parts participate in contacting transcripts. 29 Here we review the most recent experimental and computational advances for the detection of protein-RNA interactions and introduce new challenges for future developments in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it includes a classifier to allow for the classification of new data sets. 55 Dickson and Brooks present a novel strategy to determine structural ensembles for molecular dynamics simulations that uses dynamically defined sampling regions organized in a hierarchical framework. 56 Finally, Pryor and Wiener evaluated multiple existing disorder predictors for the detection of intrinsic disorder in membrane proteins.…”
mentioning
confidence: 99%